Nutrition and Intestinal Microflora - García-Elorriaga, Guadalupe; Rey-Pineda, Guillermo del (Journal of Nutritional Therapeutics, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The intestinal microflora is a complex ecosystem composed of numerous genera, species and strains of bacteria. This enormous cell mass performs a variety of unique activities that affect both the colonic and systemic physiology. The gut is colonized by a small number of bacterial species; Lactobacillus and Bifidobacteria spp. are seldom, if ever, identified. The predominant species are Enterococcus faecalis, E. coli, Enterobacter cloacae, Klebsiella pneumoniae, Staphylococcus epidermidis and Staphylococcus haemolyticus. Hygienic conditions and antimicrobial procedures strongly influence the intestinal colonization pattern. But, when large numbers of bacteria colonize the small intestine, a syndrome known as small intestinal bacterial overgrowth (SIBO) occurs. Nutrient malabsorption is a hallmark of the disorder and can result in a multitude of problems for the host. New links between SIBO and disease entities such as irritable bowel syndrome (IBS), provide intriguing new insights into the pathophysiology of the syndrome. On the other hand, in addition to its role in digestion of food in the gastrointestinal tract, intestinal microflora are also capable of biotransforming numerous drugs. Likewise, intestinal microflora may significantly modulate xenobiotic-induced toxicity by either metabolically activating or inactivating xenobiotics. We herewith present a review of the research on the importance of intestinal microflora and nutrition. Probiotics can introduce missing microbial components with known beneficial functions to the human host. Prebiotics can enhance the proliferation of beneficial microorganisms or probiotics, to maximize sustainable changes in the human microbiome. In addition, among the numerous purported health benefits attributed to probiotic bacteria, their capacity to interact with the host’s immune system is now supported by an increasing number of experiments. In addition to these, a few trials aimed at preventing chronic immune dysregulation have been reported. The identification of major immunomodulatory compounds in probiotics, and their interaction with immunocompetent cells as well as the role of secretory IgA in gut homeostasis are also evoked. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->